As manifestações do Professor Mediador Escolar e Comunitário (PMEC) acerca da resolução de conflitos: estudo sobre os elementos que constituem essa função nas escolas públicas da rede estadual paulista - Soares, Patricia Paloma Gonçalves (2016)
The focus of this research was to investigate some elements that define the role of the Mediator Instructor (of conflicts) Educational and Community (PMEC), function created by the Education Department of the state of Sao Paulo (SEESP), in 2010. We seek to describe and analyze the manifestation upon how it should be and how take place the actions of those instructors. In order to do so, interviews were conducted with the instructors and the educational supervisor, as well as the evaluation of official documents that regulate and guide the activity of conflict mediation. The objective was to analyze what define and how it is the conflict mediation in the legislation and in other documents, and in the action of PMEC, describing the elements present in the conflict mediation leading to adaptation in Adorno's perspective (2006a). The hypothesis formulated was: the creation of the function of PMEC was the found strategy by SEE-SP to deal with some problematic situations in the school, looking for not solving them, but creating mechanism that enable to live with them, especially conflicts inside of school. The analysis of the documents, as well as the report of the interviewees guided by the cited author's propositions, mainly the ones that refer to the formation field, adaptation and barbarism, enabled the confirmation of the hypothesis. It was found that the mediation carried out by the PMEC is laid on the intention of the students' adaptation to the school order; and the intention is to lead the conflicts, in view of pacification